Ensuring content validity of psychological and educational tests – the role of experts - Beck, Klaus (Frontline Learning Research, 2020)
Many test developers try to ensure the content validity of their tests by having external experts review the items in terms of relevance, difficulty, clarity, and so on. Although this approach is widely accepted, a closer look reveals there are several pitfalls that need to be avoided if experts’ advice is to be truly helpful. First, I offer a classification of tasks experts are given by test developers as reported on in the literature dealing with procedures of drawing on experts’ advice. Second, I review a sample of reports on test development (N = 72) to identify the common current procedures for selecting and consulting experts. Results indicate that often the choice of experts seems to be somewhat arbitrary, the questions posed to experts lack precision, and the methods used to evaluate experts’ feedback are questionable. Given these findings I explore in more depth what prerequisites are necessary for their contributions to be useful in ensuring the content validity of tests. In conclusion, explicit guidelines on this matter need to be elaborated and standardised (above all, by the AERA, APA, and NCME-"Standards").